Association of Blood Pressure During Thrombectomy for Acute Ischemic Stroke With Functional Outcome: A Systematic Review. Issue 10 (October 2019) - Maïer, Benjamin; Fahed, Robert; Khoury, Naim; Guenego, Adrien; Labreuche, Julien; Taylor, Guillaume; Blacher, Jacques; Zuber, Mathieu; Lapergue, Bertrand; Blanc, Raphaël; Piotin, Michel; Mazighi, Mikael
Abstract : Background and Purpose—: Optimal blood pressure (BP) targets during mechanical thrombectomy (MT) for acute ischemic stroke (AIS) are unknown, and randomized controlled trials addressing this issue are lacking. We aimed to perform a systematic review of studies evaluating the influence of periprocedural BP on functional outcome after MT. Methods—: Studies assessing periprocedural BP effect on functional outcome published after January 1st, 2012 were included in the systematic review. The PRISMA checklist and flow diagram were followed for the design and reporting of this work. Results—: Nine studies were included, for a total of 1037 patients. The heterogeneity in findings with respect to BP monitoring and studied parameters precluded a meta-analysis. Mean arterial pressure was the most frequently reported parameter to describe BP variability during MT, and systolic BP was the main parameter used to define periprocedural BP targets. Five studies suggested an association between 3 types of BP drops as predictors of poor functional outcome at 3 months: >40% drop in mean arterial pressure compared with baseline (odds ratio=2.8; [1.09–7.19]; P =0.032), lowest mean arterial pressure before recanalization (odds ratio=1.28; [1.01–1.62] per 10 mm Hg drop below 100 mm Hg; P =0.04), and MAP drops (odds ratio=4.38; [1.53–12.6] for drops >10%). Four studies did not show an association between BP during MT and functional outcome, including 3 studies with strict periprocedural systolic BP targets (within a 140–180 mm Hg). Conclusions—: BP drops during MT may be associated with a worse functional outcome. When strict systolic BP targets are achieved, no association between BP and functional outcome was also noted. Both conclusions require further evaluation in randomized studies. Abstract : Supplemental Digital Content is available in the text.